Melatonin in the promotion of health, second edition - Watson, Ronald R. (Ronald Ross) (Boca Raton, FL : CRC Press, 2012)
'This new edition presents information on how melatonin is synthesized and produced in the body as well as how this hormone affects several diseases. The book heavily focuses on prevention as well as treatment of various human disease states including behavior disorders, mental disorders, breast cancer, bone health, and gastrointestinal diseases. It covers the role of melatonin in the prevention of oxidative stress, mutagenesis, sun damage, ocular health, gut motility, and detoxification. It also presents mechanisms of melatonin action in humans including cell modulation, signaling mechanisms, protective effects, and melatonin receptors as well as its role as an antioxidant'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Melatonin -- Physiological effect; Melatonin -- Health aspects; Melatonin -- physiology; Melatonin -- therapeutic use